THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE MEDIATED JOB SATISFACTION ON CV SUKINEM BAJA INDUSTRY - Fachrurazi Fachrurazi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
An essential element in improving employee performance is a leader who can influence subordinates and actively involve them in achieving these goals through an appropriate leadership style. This study aims to uncover the relationship between dependent and independent variable variables. The type of research used in this study is quantitative research with an explanatory research approach that seeks to test the influence of dependent variables on independent variables involving 68 respondents using structural analysis methods using Partial Least Square or PLS software, resulting in the conclusion that transformational leadership style does not have a positive and insignificant effect on variables job satisfaction. Organizational culture has a positive and significant effect on job satisfaction. Transformational leadership style has no positive and insignificant effect on employee performance variables. Organizational culture has no positive and insignificant impact on employee performance variables. Job satisfaction has a positive and significant effect on employee performance. Transformational leadership style has no positive and insignificant effect on employee performance. Organizational culture positively and significantly affects employee performance by mediating job satisfaction.